Integrasi Nilai Islam dalam Kurikulum Pendidikan Dokter - Aliah, Aghar Makhzani; Rachman, Moch. Erwin; Alwi, M. Khidri (Universitas Pahlawan Tuanku Tambusai, 2025)
An integrated medical education program incorporating Islamic themes is essential for Muslim physicians. Islamic beliefs, morals, and ethics should be integrated into educational activities at both academic and professional tiers. A medical curriculum that cultivates graduates who are not only proficient doctors in their respective specialties but also embody a Muslim identity and character as medical professionals. This research use the article review methodology. The data source for this study is derived from literature accessed online, namely research findings from journal publications. The article review indicates that incorporating Islamic values into the medical education curriculum, evaluated through philosophical, pedagogical, and practical lenses, along with the associated challenges and solutions, offers a more holistic comprehension of the significance and effective methods for implementing these values.